Exploiting high rate differential algebraic space‐time block code in downlink multiuser MIMO systems. Issue 17 (25th September 2018) - Alsifiany, Fahad; Ikhlef, Aissa; Chambers, Jonathon
Abstract : This paper considers a multiuser multiple‐input multiple‐output (MIMO) space‐time block coded system that operates at a high data rate with full diversity. In particular, they propose to use a full rate downlink algebraic transmission scheme combined with a differential space‐time scheme for multiuser MIMO systems. To achieve this, perfect algebraic space‐time codes and Cayley differential transforms are employed. Since channel state information (CSI) is not needed at the differential receiver, differential schemes are ideal for multiuser systems to shift the complexity from the receivers to the transmitter, thus simplifying user equipment. Furthermore, orthogonal spreading matrices are employed at the transmitter to separate the data streams of different users and enable simple single user decoding. In the orthogonal spreading scheme, the transmitter does not require any knowledge of the CSI to separate the data streams of multiple users; this results in a system which does not need CSI at either end. With this system, to limit the number of possible codewords, a sphere decoder is used to decode the signals at the receiving end. The proposed scheme yields low complexity transceivers while providing full rate full diversity with good performance. Simulation results demonstrate the effectiveness of the proposed scheme.